2014
DOI: 10.1519/jsc.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Running Characteristics and Heart Rate Response of International and National Female Rugby Sevens Players During Competitive Matches

Abstract: This study compared the activity profile of national and international female rugby sevens players during competitive matches. Twenty rugby sevens female players were recruited, 10 were members of the Spanish National Team (26.27 ± 4.05 years, 65.39 ± 5.01 kg, 166.72 ± 6.70 cm) and 10 were amateur athletes from a Spanish rugby championship (32.12 ± 6.40 years, 66.48 ± 5.38 kg of body mass, 167.37 ± 3.02 cm). Data collection was conducted over 4 matches in each of the 2 tournaments, national and international. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 33 publications
9
47
0
8
Order By: Relevance
“…Reduction in work rate in the second half of competition was reported in rugby sevens for both internationaland national-level teams: nationallevel team average work rate decreased from 103 m/min in the first half to 88 m/min in the second half; international-level team average work rate decreased from 126 to 104 m/min (16) The one published study on women's rugby union demonstrated no reduction in second-half distance, similar to results in men's rugby union (20). Although the data do not demonstrate consistent percentage decrements, current published studies show that decreases in work rate occur regardless of competition level or sport, with the exception of rugby union.…”
Section: Distance As An Indicator Of Fatigue Within a Matchmentioning
confidence: 81%
See 3 more Smart Citations
“…Reduction in work rate in the second half of competition was reported in rugby sevens for both internationaland national-level teams: nationallevel team average work rate decreased from 103 m/min in the first half to 88 m/min in the second half; international-level team average work rate decreased from 126 to 104 m/min (16) The one published study on women's rugby union demonstrated no reduction in second-half distance, similar to results in men's rugby union (20). Although the data do not demonstrate consistent percentage decrements, current published studies show that decreases in work rate occur regardless of competition level or sport, with the exception of rugby union.…”
Section: Distance As An Indicator Of Fatigue Within a Matchmentioning
confidence: 81%
“…Several studies of elite female rugby sevens describe similar work rates (91-117 m/min) (5,16,19,24) to elite field hockey and soccer, highlighting potential common fitness attributes among these field sports at similar participant age and competition level. Similar fitness standards in elite female field sports suggest that aerobic running programming may be generalized for intermittent field sports, with sportspecific focus centering on skill sets and positional differences.…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in men's rugby sevens has characterised players and the game at elite and provincial levels of competition (Higham et al, 2012;2013a;Ross, Gill, & Cronin, 2015a;2015c;Suarez-Arrones et al, 2012b) but there is no data available on junior (under 18) male players. In female rugby sevens, the analysis of on-and off-field performance of players is predominantly in elite-level players (Clarke, Anson, & Pyne, 2015a;Clarke, Presland, Rattray, & Pyne, 2014; SuarezArrones, Nunez, Portillo, & Mendez-Villanueva, 2012a) with some research also comparing elite and provincial players (Clarke, Anson, & Pyne, 2015b;Portillo et al, 2014;Vescovi & Goodale, 2015).…”
Section: Introductionmentioning
confidence: 99%